La gestión de la ciudadanía en el Gobierno Autónomo Descentralizado de la Parroquia de San Pedro de la Bendita en el año 2020 - Fernández Rojas, Jorge Ulises (2022)
The objective of this research is to establish how citizen participation has developed in the Autonomous Decentralized Government of San Pedro de la Bendita. Through a non- experimental, descriptive and cross-sectional research, the management of citizenship was evaluated and the mechanisms of citizen participation were determined in a population of 1866 citizens, through a non-probabilistic sampling by convenience, a total of 237 investigated were determined, including the authority. The instruments applied were: interviews and surveys. The results of the investigation showed that 84.37% stated that the development of citizen participation has been low, 67.86% determined that the most used mechanism is the citizen assembly, as stated by both the citizens and the vice-president of the parish council. It was concluded that citizen participation has developed in an unfavorable way, since the citizens are unaware of this issue, demonstrating the lack of compliance with the application of these mechanisms. This research made it possible to promote talks that allow for in-depth knowledge of the mechanisms of citizen participation.